SISTEM INFORMASI KEARSIPAN POLITEKNIK NEGERI PADANG BERBASIS WEB - Rasyidah rasyidah; Yulherniwati yulherniwati; Ronal Hadi; Meri Azmi (Elektron : Jurnal Ilmiah, 2012)
The resulting of system is a web based application executed, it can be accessed by many users at the same time trough each on computer from browser by accessing the specified address. The users of this system consists of a head, department chairman, the general secretary of the department and administration of department, this system is build using PHP programming language and MySql database server. Advantages of this system is that it can save paper (paperless) and storage physical space. On this system can monitor incoming mail, incoming mail was processed, outgoing mail and letters that have been in the disposition that is in Polytecnic with available in online then this system becomes more effective performance and efficiently